234k views
0 votes
A student is trying to solve the system of two equations given below:

Equation P: y + z = 4
Equation Q: 3y + 7z = 15

Which of the following steps can be used to eliminate the y term?

A)−3(y + z = 4)
B) 3(y + z = 4)
C)−1(3y + 7z = 15)
D) −3(3y + 7z = 15)

User Htanata
by
6.2k points

2 Answers

0 votes

Answer:

A

Explanation:

User Raquelle
by
5.9k points
4 votes

Answer:

A)−3(y + z = 4)

Explanation:

Equation P: y + z = 4

Equation Q: 3y + 7z = 15

To eliminate the y term, The equations have to have the coefficients on y equal and opposite.

Equation Q has 3y, so Equation P needs -3y

Multiply equation P by -3

−3(y + z = 4)

User Marguerita
by
5.9k points